A method for the coupled solution of the filtration problem and the system of elasticity equations - Bogachev, K.Yu.; Piskovskiy, E.V.; Piatsky, G.G. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2017)
A method for the coupled solution of the vicious compressible fluid filtration problem in a porous medium and the system of elasticity equations in the case of small strains is proposed. The proposed method uses a combined algorithm based on splitting the original problem with respect to physical processes. The algorithm allows one to overcome a number of disadvantages of well-known approaches. The numerical results confirm the efficiency of the proposed method for practice.